Creativity and Innovation in Nepalese Banks - Maharjan, Pushpa (PYC Nepal Journal of Management, 2010)
This paper examines the relationship between the work environment and employee creativity and innovation in the Nepalese banks using survey method. The survey, with a set of self-administered questionnaires, was conducted in the month of November 2008 in Kathmandu valley. Of the 112 questionnaires distributed to the banks employees, 86 were returned in the usable form making the response rate of 77 per cent. The study found that challenging works impact positively on the employee creativity and innovation in the banks under study. However, the workload pressure on employees deters their creativity and innovation in the workplace.